2017
DOI: 10.1111/cpf.12432
|View full text |Cite
|
Sign up to set email alerts
|

Brachial blood flow under relative levels of blood flow restriction is decreased in a nonlinear fashion

Abstract: The decrease in brachial blood flow is not proportional to the applied relative pressure. The prescription of blood flow restriction should take into account the stimulus provided at each relative level of blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 32 publications
4
39
1
1
Order By: Relevance
“…We have previously reported that blood flow is reduced in a nonlinear fashion when applying relative levels of 10% increments of AOP in the upper body using a 5 cm wide cuff (Mouser et al, 2017a) and have further shown that this relationship is not different when applying relative pressures using 5-, 10-and 12-cm cuffs (Mouser et al, 2017b). Work performed by Hunt et al (2016) examining the decrease in blood flow at absolute increments of 10 mmHg determined the decrease to be linear.…”
Section: Introductionmentioning
confidence: 91%
“…We have previously reported that blood flow is reduced in a nonlinear fashion when applying relative levels of 10% increments of AOP in the upper body using a 5 cm wide cuff (Mouser et al, 2017a) and have further shown that this relationship is not different when applying relative pressures using 5-, 10-and 12-cm cuffs (Mouser et al, 2017b). Work performed by Hunt et al (2016) examining the decrease in blood flow at absolute increments of 10 mmHg determined the decrease to be linear.…”
Section: Introductionmentioning
confidence: 91%
“…An ongoing limitation with blood flow restriction exercise research is the inconsistency in the equipment that is used to induce BFR, while the absence of this information being reported is common. Narrower cuff widths require higher pressures to fully occlude limb blood flow, as do elastic cuffs compared with nylon cuffs, 19,76,81 so reporting only the pressure used without indication of percentage AOP/LOP or the equipment employed makes reproducibility impossible. However, this problem is mitigated with the use of individualized pressures, provided that the measure of LOP or AOP uses the same cuff as that employed during the exercise itself 19,76 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent, Mouser et al (2017) identified an inverse relationship between systolic pressure and cuff width for both men (5 cm: 160 ± 16mmHg; 10 cm: 125 ± 8; 12 cm: 122 ± 9, p<0.001) and…”
Section: Cuff Widthmentioning
confidence: 78%
“…Vascular occlusion in the research literature is typically accomplished via inflation of a pneumatic cuff placed at the proximal portion of the limb; this is further modified by differing inflation pressures as discussed and cuff widths (Mouser et al 2017). Many studies utilising occlusion have applied a single arbitrary pressure to all participants and not accounted for cuff width (Table 2.5).…”
Section: Cuff Widthmentioning
confidence: 99%
See 1 more Smart Citation